Using the Digital Leadership for Enhancing Digital Awareness in Higher Education: Penerapan Digital Leadership untuk Meningkatkan Kesadaran Digital di Perguruang Tinggi - Seri Hartati; Sumarto; Nurdin, Diding; Suryana, Asep (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Digital Leadership or digital leadership plays an important role in changing the traditional paradigm of higher education into an adaptive and innovative institution. This service is carried out at the Faculty of PSIKOSOSPOL, Abdurrab University by involving the dean, head of study program and lecturers who are expected to be able to successfully implement digital leadership. Digital leadership plays a crucial role in influencing the use of digital technology, building a culture of innovation, and creating an environment that encourages collaboration and creativity so as to improve the quality of Higher Education. The method was carried out by conducting a mini seminar in the Fakultas Psikologi dan Ilmu sosial dan Politik (FPSIKOSOSPOL) environment at Abdurrab University and at the end of the seminar a digital leadership understanding questionnaire was distributed. Questionnaires were distributed to describe understanding during the pre and post tests. The implications of this service can be an inspiration and enhance the digitall awareness for higher education institutions in facing the challenges and opportunities presented by the digital era to achieve competitive advantage, increasing quality and produce graduates who are ready to face the rapidly changing industrial world.